Retratos do invisível: revelações da fotografia em Edgar Allan Poe, Machado de Assis e Julio Cortázar - José Antônio Orlando Netto (2022)
This thesis proposes a theoretical and critical investigation into the relationship between literature and photography based on the reading of texts by Edgar Allan Poe, Machado de Assis and Julio Cortázar, authors highlighted for their paradigmatic relevance in the perception and description of the impact that the presence and the vestiges of the photographic image exert on the literary work. The use of photography is examined, in conjunction with the other narrative elements, with the purpose of discussing the way in which literature approaches and problematizes the documentary and sensorial status of photography in a specific category of this phenomenon: the processes related to approximations between the literature and certain photographic references that, despite being present as an important indication for verbal discourse, are not reproduced in the text in its iconic, visual and imagery form. The research presents a brief historiographical trajectory about the emergence of photography, about its character as an indexical sign and its impact on the formulations of culture, identifying the integration of the instruments of the photographic device, as well as its influence, in the production of the literary form. Then, the analysis seeks to highlight the incorporation of the photography theme and its technical apparatus in the literary content, as well as its possibilities of reading and interpretation in the face of formal aspects, for each of the cited authors, in matters of pragmatic, semantic and aesthetic-literary argument. In dialogue with the theoretical basis, are highlighted: the singular roles of Edgar Allan Poe, one of the founders of the approximations between literature and photography; of Machado de Assis, a pioneer in such approaches within the scope of Brazilian literature; and of Julio Cortázar, exponent of the relationships and contaminations between the literary and the photographic in the scenarios of contemporary literature. The methodology was essentially based on bibliographic research on complementary fields of knowledge, from literature, in its disruptive power, to conceptual and documentary approaches.